Preparation of Nano Niosomes Loaded with Rutin and Aloe Gel Extract - Tran, Thi Hai Yen (H. : ĐHQGHN, 2020)
Rutin is a natural flavonoid that has many effects on human health and beauty. However, rutin has low solubility and bioavailability. Niosomes are drug delivery system that enhance drug permeation of drug through the skin. Aloe is widly used in cosmetic preparations due to its antiaging, moisturizing and essential skin nutrients. Therefore, the aim of study is preparation of nano niosomes, loaded with rutin and aloe gel extraction (rutin-aloe niosomes) by thin film hydration method. Rutin niosomes was reduced size by ultrasonic method. The size and distribution of vesicles were determined by dynamic light scattering method. Drug content in niosomal suspension was determined by UV-Vis absorption spectroscopy. The results showed that rutin-aloe niosomes were prepared by thin-film hydration method using Span 60, cholesterol and rutin in molar ratio of 7:3:4 using aloe gel extract as hydration solvent. Mixture of methanol-chloroform (volume ratio 1:1) was used as solvent for solution of membrane companents for evaporation. The manufactured rutinaloe niosomes had size of about 160 nm, the entrapment efficiency was 95,57% and drug loading was 32,06%.